DISTANCE LEARNING IN A PEDAGOGICAL UNIVERSITY: PROBLEMS AND PROSPECTS - Granichina, Olga; Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article discusses the possibilities, problems and prospects of using distance learning in the process of training primary and secondary school teachers. The presented results are based on a survey of students and undergraduates of one of the largest pedagogical universities in Russia. The identified problems that was based on data processing, are presented in an ordered form. The authors suggest possible solutions to problems based on many years of experience in using distance learning technologies in training of future teachers.